Large-scale mango wine and puree production plant in the Philippines a plant design - Chua, Annabellee D.; Repollo, Anthon Jofil L.; Tejada, Kanlouise Nielsen P.
The report deals with the design of a large-scale mango wine and mango puree production plant in Bautista, Pangasinan. This includes the discussion of the main processes, the calculation of the dimensions of the major, equipment, its piping and instrumentation as well as the economic analysis of the proposed plant. A feasibility study from the previous semester establishes a demand of 15,000 liters of mango wine in the Philippines. The plant also aims to supply at least 130,000 kg of puree which corresponds to 2.5 percent of the Asia-Pacific regional demand. In a year, 9,227 kg of mangoes is needed to produce the projected demand of mango wine. There will be four batches throughout the year with each batch utilizing 2,307 kg of mangoes thereby producing 4,136 liters of wine. Each batch will last for one month and has an energy requirement of 300 kilowatt-hours. For the production of mango puree, 260,00 kg of mangoes is required. There will be 143 batches and each batch will take a day to complete the process. Each batch needs 2,307 kg of mangoes and consumes 137 kilowatt-hours. The same equipment from mango wine production will be used to produce 1,156 kg of puree. The detailed discussion on the major equipment includes the heat exchanger, mixing tank and the reactor. The operating conditions, material of construction, cost and the controls needed per equipment are taken into consideration. Overall, the plant needs a capital outlay of P 54.7 M for its equipment needs, land building and initial production. Of this, P 10M goes to the land and almost P 15M to the equipment. The plant poses a payback period of 9 years. After a twenty year period, a positive net present worth of P 4.3M is obtained. The plant has a 10.76 percent rate of return, slightly higher than the imposed 10 percent interest rate implying a profitable venture for its investors. The plant requires an 87.30 percent production in order to reach breakeven point for the first year because of the relatively small demand in wine. It should be noted that most calculations are based on very conservative projections of demand, and increases in demand will result to larger ROI, shorter payback period and large profits. Sensitivity analysis point to the mango cost price as the variable that most affects the companys profits.